The development of the creative economy in Indonesia's post-pandemic development - Kumba Digdowiseiso (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Indonesia has a great opportunity to improve national economic development through the creative economy. Entrepreneurs in the creative economy make up the largest share of all Indonesian economic activity. This research describes the development of the creative economy in Indonesia, which in the future is expected to formulate a creative industry development strategy that is right on target. The method used in this research is qualitative, using library procedures. The information presented in this study originated from literature searches from books and official websites of the authorities. The result of this research is that the creative economy has a great opportunity to develop interest and make an important contribution to development. The creative economy has the opportunity to grow in areas with the ability to generate people's energy that can turn innovative ideas into something productive. so that by maximizing the people's energy base to achieve a balanced and capable citizen who can advance ordinary safety, requires the management of innovative economic capabilities in an analytical, organized and prolonged manner.